Agroecology, Biological Control, and Catholic Social Teaching. (27th February 2021) - Whelan, Matthew Philipp
Abstract: In response to the ecological crisis, Catholic social teaching draws upon an account of natural law that appeals to natural‐ecological order and its provision of principles for tilling and keeping creation. My main contention in this article is that social teaching has insufficiently concretized the empirical entanglements of this account, along with its ecological‐agricultural implications. One consequence, as scholars like Lisa Sideris and Celia Deane‐Drummond have shown, is that social teaching, like much theological reflection upon ecology, downplays the centrality of death. While Catholic social teaching, as Óscar Romero rightly observes, must not "invade" other fields, a refusal to invade is not a refusal to engage, nor is it a refusal to learn from, or even to incorporate, wisdom from outside of itself. To this end, I argue that agroecology, a transdisciplinary science that applies ecological principles to agriculture, can help. By focusing upon an agroecological approach to the ecological management of insect herbivores ("pests") known as biological control, I show how agroecology can assist social teaching in discerning the kinds of ecological principles it calls for but does not specify—principles, in this case, related to predator‐prey dynamics in natural systems and the importance of agricultural diversification. I further argue that if social teaching continues to appeal to natural‐ecological order, it must more directly confront death's place in that order, and that the thought of Thomas Aquinas can be a helpful source. While my focus in this article is upon what social teaching can learn from agroecology, I conclude by suggesting how social teaching's account of natural law and its integral ecology can surface and develop aspects of agroecology's own, oftentimes implicit, moral vision.